Effectiveness of Providing High-Protein Snacks from Tempe on Weight Gain in Malnourished Children: A Literature Review - Susi Rahmayeni; Helmizar Helmizar; Azrimaidaliza Azrimaidaliza (Indonesian Journal of Global Health Research, 2026)
Malnutrition can lead to growth retardation. Untreated malnutrition can trigger weight faltering, which can lead to a 15-20 point decrease in IQ scores and impact a child's learning ability and cognitive function. Malnutrition in children is caused by diets that do not meet nutritional needs, particularly low-protein diets. This deficiency can potentially lead to an imbalance in the gut microbiota and interfere with optimal nutrient absorption. Therefore, innovations are needed in the form of practical, protein-rich snacks from tempe. This study aims to review the effectiveness of providing high-protein snacks from tempe on weight gain in malnourished children based on recent research findings. This study employed a literature review method by searching relevant articles online through Google Scholar, ScienceDirect, and PubMed databases. The inclusion criteria were full-text articles, involving Children aged 1 to 12  years, published within the last five years (2020–2025), written in English or Indonesian, and relevant to the research topic. The literature search was conducted through several scientific databases using relevant keywords, resulting in 434 articles in the initial identification stage and  five eligible articles were reviewed and analyzed to evaluate the impact of providing high-protein snacks from tempe on weight gain in malnourished children. Providing high-protein tempeh snacks has a significant effect on weight gain in malnourished children, with weight gain ranging from 0.2 kg to 0.5 kg. Providing high-protein snacks can increase the weight of children with malnutrition.